Tocolytic action and underlying mechanism of galetin 3,6-dimethyl ether on rat uterus - Juliana da Nóbrega Carreiro; Iara Leão Luna de Souza; Joedna Cavalcante Pereira; Luiz Henrique César Vasconcelos; Rafael de Almeida Travassos; Barbara Viviana de Oliveira Santos; Bagnólia Araújo da Silva (BMC, 2017)
Abstract Background Galetin 3,6-dimethyl ether (FGAL) is a flavonoid isolated from aerial parts of Piptadenia stipulacea. Previously, FGAL was shown to inhibit both carbachol- and oxytocin-induced phasic contractions in the rat uterus, which was more potent with oxytocin. Thus, in this study, we aimed to investigate the tocolytic action mechanism of FGAL on the rat uterus. Methods Segments of rat uterus ileum were suspended in organ bath containing modified Locke-Ringer solution at 32 °C, bubbled with carbogen mixture under a resting tension of 1 g. Isotonic contractions were registered using kymographs and isometric contractions using force transducer. Results FGAL was more potent in relaxing uterus pre-contracted with oxytocin than with KCl. Additionally, FGAL shifted oxytocin-induced cumulative contractions curves to the right in a non-parallel manner, with Emax reduction, indicating a pseudo-irreversible noncompetitive antagonism of oxytocin receptors (OTR) or a downstream pathway target. Moreover, FGAL shifted CaCl2-induced cumulative contraction curves to the right in a non-parallel manner in depolarizing medium, nominally without Ca2+, with Emax reduction, suggesting the inhibition of Ca2+ influx through CaV. The relaxant potency of FGAL was reduced by CsCl, a non-selective K+ channel blocker, suggesting positive modulation of these channels. Furthermore, in presence of apamin, 4-aminopyridine, glibenclamide or 1 mM TEA+, the relaxant potency of FGAL was attenuated, indicating the participation of SKCa, KV, KATP and highlighting BKCa. Aminophylline, a non-selective phosphodiesterase (PDE) blocker, did not affect the FGAL relaxant potency, excluding the modulation of cyclic nucleotide PDEs pathway by FGAL. Conclusion Tocolytic effect of FGAL on rat uterus occurs by pseudo-irreversible noncompetitive antagonism of OTR and activation of K+ channels, primarily BKCa, leading to calcium influx reduction through CaV.